Prediction of particulate fouling in full-scale reverse osmosis plants using the modified fouling index – ultrafiltration (MFI-UF) method - Mohanad Abunada; Nirajan Dhakal; Raffay Gulrez; Pamela Ajok; Yuke Li; Almotasembellah Abushaban; Herman Smit; David Moed; Noreddine Ghaffour; Jan C. Schippers; Maria D. Kennedy (Desalination, 2023)

Plant traits determining biogeomorphic landscape dynamics: A study on clonal expansion strategies driving cliff formation at marsh edges - Haobing Cao; Zhenchang Zhu; Peter M.J. Herman; Stijn Temmerman; Jaco de Smit; Liquan Zhang; Lin Yuan; Tjeerd J. Bouma (Limnology and Oceanography, 2021)
Despite the well‐recognized importance of plant traits for biogeomorphic development of landscapes, our understanding remains limited of how species‐specific plant traits respond to and serve as drivers for the sedimentary dynamics within a biogeomorphic landscape. By manipulating a series of laboratory experiments, using mesocosms and a flume, we examined how species‐specific differences in expansion strategy, i.e., clonal step‐length of laterally expanding tillers, both respond to sediment type and drive cliff formation and persistence. We compared three marsh species, with contrasting clonal expansion traits, that are dominant in many estuaries worldwide: Spartina anglica , Scirpus maritimus , and Phragmites australis . Our results revealed that S. anglica tussocks tend to have high shoot density due to a short clonal expansion step‐length, whereas S. maritimus tussocks were much more diffuse and tend to have a longer clonal expansion step‐length. P. australis showed intermediate traits. Clonal expansion step‐length did show within‐species variation in response to sediment texture, but species‐specific differences remained the most important. Species with smaller clonal step‐lengths, such as S. anglica in this study, are more likely to induce cliffs at the marsh edge by driving formation of larger cliff heights and also having lower capacity to grow out from cliffs. Our findings thus illustrate how dynamic landscape features like cliffs at marsh edges depend on the clonal expansion traits of the dominant species. This enhances current understanding of the formation and development of marsh edges, and is instructive for understanding the role of species‐specific traits in driving distinct biogeomorphic landscape dynamics.

Increased herpes zoster risk associated with poor HLA-A immediate early 62 protein (IE62) affinity - Pieter Meysman; Nicolas De Neuter; Esther Bartholomeus; George Elias; Johan Van den Bergh; Marie-Paule Emonds; Geert W. Haasnoot; Steven Heynderickx; Johan Wens; Nele R. Michels; Julien Lambert; Eva Lion; et al. (Immunogenetics, 2018)

Impact of tropical convection and ENSO variability in vertical distributions of CO and O3 over an urban site of India - L. K. Sahu; Varun Sheel; M. Kajino; M. Deushi; Sachin S. Gunthe; P. R. Sinha; Ravi Yadav; Devendra Pal; P. Nedelec; Valérie Thouret; Herman G. Smit (Climate Dynamics, 2017)

Gas Response Behaviour and Photochemistry of Borondiketonate in Acrylic Polymer Matrices for Sensing Applications - Juan Diego Arias Espinoza; Viacheslav Sazhnikov; Edsger C. P. Smits; Dmirity Ionov; Yuriy Kononevich; Iryna Yakimets; Mikael Alfimov; Herman F. M. Schoo (Journal of Fluorescence, 2014)

Emerging evidence for CHFR as a cancer biomarker: from tumor biology to precision medicine - Sarah Derks; Arjen H. G. Cleven; Veerle Melotte; Kim M. Smits; Johann C. Brandes; Nilofer Azad; Wim van Criekinge; Adriaan P. de Bruïne; James G. Herman; Manon van Engeland (Cancer and Metastasis Reviews, 2013)

Climatology of tropospheric ozone and water vapour over Chennai: a study based on MOZAIC measurements over India - L. K. Sahu; S. Lal; Valérie Thouret; Herman G. Smit (International Journal of Climatology, 2011)
Climatology of tropospheric ozone (O 3 ) and water vapour (H 2 O) over a metro city of Chennai in southern India has been presented based on the M easurements of OZ one and water vapour by A irbus I n‐service Air C raft (MOZAIC) data during 1996–2001. The seasonal trends in mixing ratio of O 3 are discussed in view of annual changes in the transport pattern, rainfall, and its relationship with ambient H 2 O. The vertical distributions of both O 3 and H 2 O show large seasonal variations. The observed high mixing ratios of O 3 in winter and spring months can be attributed to long‐range transport of pollutants by the northwesterly winds associated with winter monsoon circulation. The lowest mixing ratio of 15 ppbv of O 3 from July to September coincides with the summer monsoon circulation over Indian subcontinent. The surface level mixing ratio of O 3 was observed to be below 30 ppbv throughout the year. On the other hand, monthly rainfall and vertical distributions of H 2 O show just opposite seasonal variations to that of O 3 mixing ratio. Chennai is a coastal city; therefore, the seasonal change in surface wind flow causes large variability in H 2 O concentrations of 6–30 g/kg in the lower troposphere. More or less similar annual patterns of mixing ratios of O 3 and H 2 O are repeated during different years of 1996–1998, except for some small‐scale differences. High level of O 3 mixing ratio, particularly during the early winter months of year 1997, seems unusual as we do not see such trends for other year of measurements over Chennai. The case studies of profiles of O 3 , relative humidity (RH), and temperature in view of long‐range transport over Chennai during the different seasons have been also discussed. Significant enhancements in tropospheric O 3 were observed over Chennai due to transport of air from forest fire regions of Indonesia during October 1997. Copyright © 2010 Royal Meteorological Society

Treatment efficacy in a soman-poisoned guinea pig model: added value of physostigmine? - Marloes J. A. Joosen; August B. Smit; Herman P. M. van Helden (Archives of Toxicology, 2011)

Timing of eclogite facies metamorphism in the southernmost Scandinavian Caledonides by Lu–Hf and Sm–Nd geochronology - Matthijs A. Smit; Erik E. Scherer; Michael Bröcker; Herman L. M. van Roermund (Contributions to Mineralogy and Petrology, 2010)

Design, Construction, and Testing of an Automated NIR In-line Analysis System for Potatoes. Part II. Development and Testing of the Automated Semi-industrial System with In-line NIR for the Characterization of Potatoes - Kommer Brunt; Bernard Smits; Herman Holthuis (Potato Research, 2010)

Seasonality of tropospheric ozone and water vapor over Delhi, India: a study based on MOZAIC measurement data - Lokesh K. Sahu; Shyam Lal; Valérie Thouret; Herman G. Smit (Journal of Atmospheric Chemistry, 2009)

The Impact of Bioturbation by Small Mammals on Heavy Metal Redistribution in an Embanked Floodplain of the River Rhine - Sander Wijnhoven; Ivo Thonon; Gerard Van Der Velde; Rob Leuven; Mathilde Zorn; Herman Eijsackers; Toine Smits (Water, Air, & Soil Pollution, 2006)

On the Exchange of NO3 Radicals with Aqueous Solutions: Solubility and Sticking Coefficient - Karin Thomas; Andreas Volz-Thomas; Djuro Mihelcic; Herman G. J. Smit; Dieter Kley (Journal of Atmospheric Chemistry, 1998)